2014
DOI: 10.1063/1.4884416
|View full text |Cite
|
Sign up to set email alerts
|

Sheet resistance under Ohmic contacts to AlGaN/GaN heterostructures

Abstract: For the determination of specific contact resistance in semiconductor devices, it is usually assumed that the sheet resistance under the contact is identical to that between the contacts. This generally does not hold for contacts to AlGaN/GaN structures, where an effective doping under the contact is thought to come from reactions between the contact metals and the AlGaN/GaN. As a consequence, conventional extraction of the specific contact resistance and transfer length leads to erroneous results. In this Let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…We investigated the compositional and morphological changes in Al 0.24 Ga 0.76 N surfaces etched by the CF 4 and Ar plasmas at various gas pressures and etching times. The comparison between the results induced by the CF 4 and Ar plasma etchings clarified the contribution of fluorine impurities incorporated in the surface by the CF 4 plasma etching.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We investigated the compositional and morphological changes in Al 0.24 Ga 0.76 N surfaces etched by the CF 4 and Ar plasmas at various gas pressures and etching times. The comparison between the results induced by the CF 4 and Ar plasma etchings clarified the contribution of fluorine impurities incorporated in the surface by the CF 4 plasma etching.…”
Section: Discussionmentioning
confidence: 99%
“…We also checked the etch depths of the surfaces because they are generally relevant to the compositional and morphological changes in the surfaces. We discuss a difference between the surface characteristics induced by the CF 4 and Ar plasma etchings in terms of the incorporated fluorine impurities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Si implanted processes are also in use to make the GaN heavily n‐type before the formation of Ohmic contacts . It is generally understood that the dominant mechanism for electron transport is tunneling between TiN and heavily doped GaN formed due to nitrogen vacancy . Here, we have shown that intentional traps created by a boron (B) implantation can significantly reduce the contact resistance for GaN‐based heterostructures.…”
Section: Introductionmentioning
confidence: 89%